LEVELS OF PHYSICAL ACTIVITY IN PUERTO RICAN FEMALE ADOLESCENTS: A PILOT STUDY - Álvarez, Amaury J. (2013)
Physical activity (PA) is known to decline and obesity to increase from childhood to adulthood. During adolescence, girls are particularly vulnerable to both physical inactivity and overweight leading to obesity. Childhood and adolescent obesity is a known health problem in Puerto Rico; however, PA has not been well described in this population. The purpose of this study was to evaluate PA levels and factors influencing PA in a group of Puerto Rican adolescent females. Forty participants wore an accelerometer during six consecutive days and completed a PA questionnaire. Participants were divided in two groups according to age (11-13 and 14-16 years). Parents completed a socio-demographic and PA questionnaire. ANOVA and independent t-tests were used to identify differences in moderate to vigorous PA (MVPA) by age group, and between adolescents and their parents. Multiple regression analysis was performed to identify factors related to PA. MVPA averaged 87(54) min/week with no differences between age groups: 11-13 y.o. =87(58) and 14-16 y.o. =86(50) min/week (p=.95).A significant association was observed between parents and adolescents’ MVPA (r=0.67, p<.01). The most powerful predictors of the adolescents’ MVPA were parental MVPA and the days parents shared PA with their daughters. Puerto Rican female adolescent participants showed PA levels below the minimal recommendation for health. School-based health promotion interventions designed to help increase PA levels in this population must consider parental involvement.